Where are my sources? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The recent changes in Spore have upset Fekade H Mariam of Addis Ababa, Ethiopia: 'The Information Source section is missing, and the Courses and Conferences section too. Please assure me that you are not dropping these two sections, since they mean...